Noise exposure and induced hearing loss to workers in small and large scale industries - Farrell Luka, Moses; Akun, Ertan (International Journal of Engineering and Technology, 2018)
The purpose of this research is to determine the level of noise exposure to workers and to recommend how to manage the occupational high level of noise, understanding the workers noise exposure and providing personal ear protectors is the responsibility of employers. After visiting almost all the industries it was noticed that none of these industries are following these requirements. Knowing that expo- sure to excessive noise can cause health problems including temporary or permanent hearing loss, concentration problems, stress, nerv- ousness, sleeping problems and fatigue. The noise levels was measured in different industrial settings in North Cyprus using a noise detecting equipment, cirrus 273 integrated sound level meter with octave band filters. The Safety and health standards for noise exposure were used as the benchmark for our data analysis. Questionnaires were designed to determine how much employees were affected by high noise levels in the workplace. Dataâ€™s were analyzed using SPSS statistical program. Survey responses identified the most likely problems faced by industrial workers in North Cyprus. Sound level mapping informed worker noise exposure. It was found the most of the workers were exposed to high level of noise so therefore future studies will focus on industries with the highest noise levels, monitor- ing worker noise exposure using a dosimeter. The use of engineering method is considered best in reducing the high level of noise in these Industries.Â Â